Penerapan Model STAD Berbasis Scientific untuk Meningkatkan Aktivitas dan Hasil Belajar Tematik - Wahyu Dinar Febriyani; Nyoto Hardjono (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This study aims to improve thematic learning outcomes through the application of a scientific-based STAD learning model. The subjects of the study were students of grade 3A SDN Salatiga 06. The type of research used was using the Stringer model. Data collection techniques carried out are observation, documentation, and tests. This research was carried out in two cycles. The results showed: (1) pre-cycle activity score in grade 4 was 73% with an average value of 74.50 and pre-cycle learning completeness scores of 76% with an average value of 77.50; (2) The score of student activity in the first cycle was 74% with an average value of 75.20 and in the second cycle was 81.50% with an average value of 81.40; (3) The learning completeness of students in the first cycle is 71.88% with an average value of 75.15 and in the second cycle is 81.25% with an average value of 83.25. From these data shows that the research is appropriate which means that the indicator of success has been achieved.